Economics of fisheries in selected Barangays of Oton and Tigbauan, Iloilo. - Diaz, Janice I.
This research project examines the feasibility and applicability of having fisher folk cooperative and described socioeconomic determinants that persuade the fishers to join in the fisher folk cooperative. It also describes the living conditions of fishers and the costs and returns of their fishing operation. Most of the respondents were motorized boat owners totaling 41 fishers, 38 were non-motorized boat owners and 21 fishing crew (did not own any fishing boat). The results show that fishers were willing to join in a fisher folk cooperative provided that there is proper management governing the said cooperative. The factors that positively influenced the fishers' participation were the house hold size, number of years of education and the benefit that the fishers will get if they will be a member of the cooperative. Costs and returns analysis showed that in both towns, there is positive economic profit, financial profit and gross profit. This is in the case of a short-run period only, but it is believed that in the long run, profit would be dissipated due to the virtual open-access attribute of the fishery resource. It should be noted that any one interested and has capital can just start a fishing venture purchasing the fishing assets needed.